The FMS-like tyrosine kinase-3 ligand/lung dendritic cell axis contributes to regulation of pulmonary fibrosis. Issue 10 (10th May 2019) - Tort Tarrés, Meritxell; Aschenbrenner, Franziska; Maus, Regina; Stolper, Jennifer; Schuette, Lisanne; Knudsen, Lars; Lopez Rodriguez, Elena; Jonigk, Danny; Kühnel, Mark Philipp; DeLuca, David; Prasse, Antje; Welte, Tobias; et al.
Abstract : Rationale: Dendritic cells (DC) accumulate in the lungs of patients with idiopathic lung fibrosis, but their pathogenetic relevance is poorly defined. Objectives: To assess the role of the FMS-like tyrosine kinase-3 ligand (Flt3L)-lung dendritic cell axis in lung fibrosis. Measurements and main results: We demonstrate in a model of adenoviral gene transfer of active TGF-β1 that established lung fibrosis was accompanied by elevated serum Flt3L levels and subsequent accumulation of CD11b pos DC in the lungs of mice. Patients with idiopathic pulmonary fibrosis also demonstrated increased levels of Flt3L protein in serum and lung tissue and accumulation of lung DC in explant subpleural lung tissue specimen. Mice lacking Flt3L showed significantly reduced lung DC along with worsened lung fibrosis and reduced lung function relative to wild-type (WT) mice, which could be inhibited by administration of recombinant Flt3L. Moreover, therapeutic Flt3L increased numbers of CD11b pos DC and improved lung fibrosis in WT mice exposed to AdTGF-β1. In this line, RNA-sequencing analysis of CD11b pos DC revealed significantly enriched differentially expressed genes within extracellular matrix degrading enzyme and matrix metalloprotease gene clusters. In contrast, the CD103 pos DC subset did not appear to be involved in pulmonary fibrogenesis. Conclusions: We show that Flt3L protein and numbers of lung DC are upregulated in mice and humans during pulmonary fibrogenesis, and increased mobilisation of lung CD11b pos DC limits the severity of lung fibrosis in mice. The current study helps to inform the development of DC-based immunotherapy as a novel intervention against lung fibrosis in humans.